Optimalisasi Peran Sekolah dan Keluarga dalam Menumbuhkan Kesadaran Pengelolaan Sampah pada Anak Usia Dini - Wasito, Hendri; Nuryanti, Nuryanti; Baroroh, Hanif Nasiatul; Utami, Vitis Vini Fera Ratna; Sholihat, Nia Kurnia; Hasan, Nahrul; Wahyudi, Ari; Sari, Suci Wulan (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Waste management remains a critical issue in schools due to low awareness of clean living and limited knowledge. This community service aimed to foster early waste awareness at Azalia Integrated Islamic Kindergarten using a Participatory Action Research (PAR) approach. Activities included initial observation, game-based education, teacher-parent training, improved educational tools, and mentoring. Evaluations through pre- and post-tests showed significant improvement in both student and parent understanding of waste sorting. The program cultivated a collective awareness of waste management and is expected to continue as part of a clean and healthy life.